Arab Republic of Egypt : Fifth Review Under the Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Arab Republic of Egypt's Fifth Review Under the Extended Fund Facility (EFF). Macroeconomic performance has remained strong in 2018/19, supported by continued sound policy implementation. The report highlights that monetary policy remains anchored by the medium-term objective of bringing inflation to single digits. Core inflation appears to be well contained, however the central bank should remain cautious until disinflation is firmly entrenched. Exchange rate flexibility remains essential to improve resilience to shocks and preserve competitiveness. The outlook remains favorable and provides an opportune juncture to further advance structural reforms to support more inclusive private-sector led growth and job creation. The authorities have launched important reforms of competition policy, public procurement, industrial land allocation, and state-owned enterprises, and sustained implementation will be essential to ensure that statutory changes achieve meaningful results in the business climate. Sustained efforts are needed to advance reforms in competition, industrial land allocation, and governance of state-owned enterprises.